(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to determine: (1) The effect of brand equity on purchasing decisions, (2) The effect of perceived quality on purchasing decisions, (3) The effect of brand association on purchasing decisions, and (4) The effect of brand loyalty on purchasing decisions. This type of research is a survey research using a questionnaire. The population in this study were all consumers of LG brand LED TVs in the Special Region of Yogyakarta. The samples used are consumers who have made purchases and consumers who use LG branded LED TVs. The sampling method used accidental sampling with a number of respondents 100 people. Data were collected using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study indicate that: based on the results of the t test (1) Brand Equity does not have a significant effect on the decision to buy LED TV products with the LG brand in Yogyakarta with a significance value of 0.427greather than 0.05. (2) Perception of quality does not have a significant effect on purchasing decisions for LG brand LED TV products in the Special Region of Yogyakarta with a significance value of 0.222greather than 0.05. (3) Brand Association has a significant effect on purchasing decisions for LG brand LED TV products in Yogyakarta with a significance value of 0.037 less than0.05. (4) Brand Loyalty has a significant effect on purchasing decisions for LG LED TV products in the Special Region of Yogyakarta with a significance value of 0.000greather than 0.05. Meanwhile, based on the F test, it shows that brand association and brand loyalty simultaneously influence the decision to buy LED TV products with the LG brand in Yogyakarta, with a calculated F value of 56,968greather than 0.05 with a significance value of 0.000 less than0.05.